Cardiovascular safety of sulphonylureas: over 40 years of continuous controversy without an answer. Issue 6 (20th March 2015) - Abdelmoneim, A. S.; Eurich, D. T.; Light, P. E.; Senior, P. A.; Seubert, J. M.; Makowsky, M. J.; Simpson, S. H.
<x xml:space="preserve">Abstract</x> More than 40 years after publication of the University Group Diabetes Program trial, the cardiovascular safety of sulphonylureas is still contentious. Although several hypotheses linking sulphonylureas to adverse cardiovascular effects exist, none provide conclusive evidence. Adding to the controversy, current clinical trials and observational studies provide inconsistent, and sometimes conflicting, evidence for the cardiovascular effects of sulphonylureas. Overall, observational evidence suggests that an increased risk of adverse cardiovascular outcomes is associated with sulphonylureas; however, these data may be subject to residual confounding and bias. Although evidence from randomized controlled trials has suggested a neutral effect, the majority of these studies were not specifically designed to assess the effect of sulphonylureas on adverse cardiovascular event risk. Current ongoing large clinical trials may provide some clarity on the cardiovascular safety of sulphonylureas, but the results are not expected for several years. With the continued uncertainties concerning the cardiovascular safety of all antidiabetic drugs, a clear answer with regard to sulphonylureas is warranted. The objectives of the present article were to provide an overview of the controversy surrounding sulphonylurea‐related cardiovascular effects, to discuss the limitations of the current literature, and to provide recommendations for future studies aiming to elucidate the true relationship between sulphonylureas and adverse cardiovascular effects in people with type 2 diabetes.